«We are not here to entertain you». Sambhaji Bhagat’s voice of presence - Sara Roncaglia (Archivio Antropologico Mediterraneo)
Sambhaji Bhagat is the heir of a centuries-old tradition of songs of participation, protest and peace, whose life blood comes from the folklore heritage of Maharashtra. Finding inspiration in such lok shahirs, bards, as Annabhau Sathe and Amar Sheikh, Sambhaji Bhagat is one of the main innovators of the shahir tradition. The article describes, through his words and his songs, the life story of an artist who attempts, with his lyrics, to give voice in Mumbai to the outcast, to those who today most suffer from the processes of marginalization and expulsion.